2011
DOI: 10.1016/j.athoracsur.2011.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Learning Curve for Endoscopic Vein Harvest on Conduit Quality and Early Graft Patency

Abstract: Background Recent studies have suggested that endoscopic vein harvest (EVH) compromises graft patency. To test whether the learning curve for EVH alters conduit integrity owing to increased trauma compared with an open harvest, we analyzed the quality and early patency of conduits procured by technicians with varying EVH experience. Methods During coronary artery bypass grafting, veins were harvested open (n = 10) or by EVH (n = 85) performed by experienced (>900 cases, >30/month) versus novice <100 cases, <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Previous studies have also discussed the impact of the operator's learning curve on vein injury during harvest, 31,38 with reports suggesting a minimum number ranging from 20 to 100 cases to complete the learning curve. 15,31,38 In their study, Desai et al 38 showed that inexperienced operators are 50% more likely to cause intimal and deep vessel injury to the saphenous vein graft, which increases risk of failure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have also discussed the impact of the operator's learning curve on vein injury during harvest, 31,38 with reports suggesting a minimum number ranging from 20 to 100 cases to complete the learning curve. 15,31,38 In their study, Desai et al 38 showed that inexperienced operators are 50% more likely to cause intimal and deep vessel injury to the saphenous vein graft, which increases risk of failure.…”
Section: Discussionmentioning
confidence: 97%
“…15,31,38 In their study, Desai et al 38 showed that inexperienced operators are 50% more likely to cause intimal and deep vessel injury to the saphenous vein graft, which increases risk of failure. This underlines the importance of safe and reliable training and monitoring to minimize the negative impact of the learning curve on vein graft quality.…”
Section: Discussionmentioning
confidence: 98%
“…However, this has changed in the past years with "novice" level practitioners becoming experts. It has recently been found that when procured by expert level harvesters the physical damage to the vein is similar to that of open harvest [12], [13]. Thus, it is hypothesized that EVH and open harvest when performed by an expert will have similar patency rates if all other factors are equal.…”
Section: How Vein Harvesting Methods Can Affect Patency Ratesmentioning
confidence: 99%
“…However, EVH has been associated with increased endothelial injury, which may have significant negative consequences including graft patency and possibly long-term survival [68,69]. Desai et al recently demonstrated using optical coherence tomography that EVH operators had a steep learning curve with regard to subtle RSVG injuries and that vein grafts with four or more intimal or medial dissections showed significantly worse early patency rates than those with fewer intimal injuries (67% vs. 96%) [70]. In contrast, when RSVGs are harvested using a "no touch" technique, better patency results have been noted.…”
Section: Saphenous Vein Graft Conduitsmentioning
confidence: 99%